(untitled) (Research, Society and Development, 2022)
The daily pressures exerted by urban centers, added to the absence of green areas, end up promoting great damage to the quality of life of the resident population. This study aimed to evaluate the influence of a green park in the central area in Dourados, MS, Brazil, on thermal and sound comfort through environmental indicators. The following measurements were taken: air temperature, relative air humidity, light incidence, and noise variation at sampling points in the Arnulpho Fioravante green park and adjacent areas. The thermal discomfort index (TDI), which considers the variables air temperature and relative air humidity, was also adopted. TDI and noise results indicated that the park has little influence on adjacent areas. On the other hand, the park area with the highest plant density showed significant TDI values, classifying it between “feeling comfortable” and “feeling partially uncomfortable.” Areas of the city and the park without vegetation had many “feeling uncomfortable” ratings. Moreover, the vegetation may have acted as a filter to minimize urban noise. Our results indicate that urban green areas are important components in maintaining the population’s quality of life, provided they have good planning and management of available forest resources.